PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN DI LEMBAGA PERKREDITAN DESA (LPD) KEROBOKAN - I Ketut Suparman; I Nengah Aristana; I Wayan Arta Artana (Universitas Triatma Mulya, 2022)
The purpose of this research was to determine whether communication and motivation have an influence on employee performance. The respondents in this research were 71 employees. The data analysis used is Validity and reliability tests, multiple linear regression analysis, classical assumption evaluation, t-test analysis, and decision analysis. Based on the results of the study, communication is positive and significant influence partially between employee performance at the Kerobokan Village Credit Institution (LPD). Meanwhile, motivation is positive and significant influence partially between employee performance (LPD). Based on the findings, it is recommended that we continue to sustain and enhance contact in order to build positive relationships with leaders and coworkers, and to be able to take ownership of their work for the company's benefit.